Changing role of millennial accountants in the information revolution era (Industry 4.0) and challenges in the society generation scope (Society 5.0) - Muhammad Zharfan; Hendra Harmain (Institute of Computer Science (IOCS), 2023)
This study aims to analyze and test the influence of Revolution information (Industry 4.0) on the role of Accountants millennials with challenges on the scope generation community (society 5.0) as a moderating variable. This research uses approach descriptive and associative quantitative. The population in this study are Accountants and student candidates Accountants in Medan City with the selected sample by random sampling amounting to 110 people. Data analysis techniques using Structural Equation Model (SEM) with tools help Smart PLS V 3.2. Research Results show that there is an influence of Revolution Industry 4.0 towards changing the role of the millennial accountant. And challenge on the scope generation community (society 5.0) moderates the changing role of Accountants millennials in the era of industry 4.0.